Demographics as Variables in Assessing the Study Habits of High School Students in a Catholic School - Judy N. Fernandez; Celo I. Magallanes (Philippine Social Science Journal, 2020)
Study habits and skills differ from one person to another. Effective study habits are instrumental for students to gain mastery of a topic learned and ensure good academic performance. Study habits that students employ to cope with their lessons are ways, techniques, and learning styles which may include, but not limited to, time management or the number of hours spent studying their lessons and making assignments; study environment, test-taking skills which include students’ readiness or preparedness in taking tests; note-taking skills or student’s efficiency in taking down notes during class hours or while reading; reading skills which are the student’s ability to understand and comprehend lessons, tests, and reading materials; writing skills or the ability to observe correct grammar and to write effectively; and math skills or the facility and ease in solving math problems. With the advancement of technology, students nowadays engage themselves more in gadgets and spend more time in electronic media and social media; thus, students' study habits are slowly deteriorating when it comes to frequency and quality. Hence, this study was conducted to determine the level of study habits in relation to selected demographics of high school students in a Catholic School in Antique during the school year 2019-2020. Likewise, it measured the relationship between the demographic variables and their extent of study habits and determined which areas predict the students' study habits.